2011
DOI: 10.1073/pnas.1104692108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between topological order and glass forming ability in densely packed enstatite and forsterite composition glasses

Abstract: The atomic structures of magnesium silicate melts are key to understanding processes related to the evolution of the Earth's mantle and represent precursors to the formation of most igneous rocks. Magnesium silicate compositions also represent a major component of many glass ceramics, and depending on their composition can span the entire fragility range of glass formation. The silica rich enstatite (MgSiO 3 ) composition is a good glass former, whereas the forsterite (Mg 2 SiO 4 ) composition is at the limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
111
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 36 publications
(48 reference statements)
21
111
0
Order By: Relevance
“…The coordination number for O 2-in these glasses likely varies as much and as a function of glass composition. Kohara et al 80,81 found free oxide in magnesium silicate glasses, and although they did not address the O 2-coordination number, their diagrams (e.g., fig. 4 80 ) indicate 2 and 3 coordinate free oxide.…”
Section: Oxygen Coordination and Chemical Shiftsmentioning
confidence: 97%
“…The coordination number for O 2-in these glasses likely varies as much and as a function of glass composition. Kohara et al 80,81 found free oxide in magnesium silicate glasses, and although they did not address the O 2-coordination number, their diagrams (e.g., fig. 4 80 ) indicate 2 and 3 coordinate free oxide.…”
Section: Oxygen Coordination and Chemical Shiftsmentioning
confidence: 97%
“…AsS 2 has a 064202-5 much lower density and a much larger cavity volume (37.8 %) than AgAsS 2 (4.8%) and is clearly porous at the atomistic level. The cavity volume of a-SiO 2 was 31.9% with the same parameter set [45]. The trechmannite structure may be viewed as a defective PbS (galena) structure.…”
Section: Cavity Distributionsmentioning
confidence: 99%
“…It has also been suggested Kohara: Atomistic and electronic structures of functional disordered materials revealed by a combination of quantum-beam measurements and computer simulations JCS-Japan that the small cages are topologically disordered, 21) resulting in a broad distribution of ring sizes from threefold to twelvefold rings centered at sixfold rings. 13) This is reflected in S NN (Q) for l-SiO 2 [ Fig. 10(A)], where the FSDP is broader than the corresponding Bragg peak in the crystalline phase (¢-cristobalite, c-SiO 2 ), where only a sixfold ring contributes.…”
Section: ¹1mentioning
confidence: 99%